Effects of group sports activities on physical activity and social interaction abilities of children with autism spectrum disorders - Yu Xing; Yu Xing; Shuaibin Huang; Yatong Zhao; Xueping Wu (Frontiers in Psychology)
IntroductionGroup sports activities have been demonstrated to have an impact on the physical activity and social interaction abilities of children with autism spectrum disorder (ASD).MethodsThus, this work, taking different types of group sports as the primary variable, explored the impact of 12-week group sports activities on the physical activity and social interaction abilities of children with ASD. A quasi-experimental design was used to divide 21 children with ASD into Experimental group (N = 11) and Control group 1 (N = 10), while healthy children of the same age were selected as Control group 2 (N = 12). The experimental group performed group sports activities for 60 min/time, 4 times/week, for a total of 12 weeks, while the control group maintained the traditional sports activities of Peizhi School. Physical activity was monitored using a three-axis accelerometer (Model: ActiGraph GT3X+), and social interaction ability was measured using the playground observation of peer engagement (POPE) observation scale to evaluate the social interaction states of children in the experimental group after the physical activities.Results and discussionAfter the intervention, the sitting time of children in the experimental group was significantly reduced (t = −12.735, p < 0.001, Cohen d = 2.75), and the time of moderate and high-intensity physical activity was significantly increased (t = −8.79, p < 0.001, Cohen d = 1.82). In social interaction ability, the duration of loneliness was significantly reduced (t = −2.567, p < 0.017, Cohen d = 0.57), and the duration of joint participation (t = −3.009, p < 0.007, Cohen d = 0.02) and the regular game (t = −2.511, p < 0.026, Cohen d = 0.46) were significantly increased, respectively. 4 weeks after the intervention, the sedentary behavior and loneliness of the experimental group both continued to decrease. Group physical activities can improve the physical activity levels and social interaction skills of children with ASD and have a good effect on the maintenance.